Purchase Decisions Influenced by Product Quality, Price Perception, and Service Quality - Yuwanna, Indy; Tarigan, Chatarina Yunita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The increasing competition in the coffee shop industry has encouraged local businesses to continuously improve their product and service quality to meet consumer expectations. This study aims to examine the influence of product quality, price perception, and service quality on consumers who had visited Kopi Pintu Taman at least once or twice. Data were collected using a structured questionnaire and analyzed through multiple linear regression using SPSS 25. the findings indicate that all three variables have a significant and positive impact on purchasing decisions, with product quality being the most dominant factor. These results imply that small and medium sized coffee shop businesses must maintan high product standards, fair pricing, and consistent service to enhance cosumer satisfaction and remain competitive. This research provides insights for practitioners in the food and beverage sector and contributes to the existing literature by highlinghting consumer behavior in local coffee shop contexts.